Pengaruh Pengumuman Kebijakan Dividen terhadap Volatilitas Harga Saham - Yani Riyani (Eksos, 2019)
This study aims to determine the effect of dividend policy announcements on stock price volatility. This research is an event study, with a period of observation 10 days before and after dividend announcement. According to the purposive sampling of 30 companies incorporated in the JII there are 20 companies that meet the criteria to be sampled. The variable used in this study is dividend policy announcements which are proxied by abnormal returns and stock price volatility. By using simple linear regression analysis, the results of the study found that the dividend announcement policy affects the volatility of stock prices. This means that dividend policy announcements contain information that causes shares to react. The results of this study are consistent with the dividend signaling theory which states that dividend policy announcements contain information that can cause stock prices to react.